1974
DOI: 10.1136/adc.49.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal absorption of calcium and magnesium in hepatobiliary disease in infancy

Abstract: Archives of Disease in Childhood, 49, 90. Intestinal absorption of calcium and magnesium in hepatobiliary disease in infancy. The intestinal absorption of calcium and magnesium was measured by metabolic balance studies in 6 normal infants, 13 infants with biliary atresia, 5 infants with successfully repaired biliary atresia, 7 infants with neonatal hepatitis, and 2 infants with choledochal cyst. The absorption of both elements was impaired in these disorders. The malabsorption of these elements was most marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

1974
1974
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
2
7
0
1
Order By: Relevance
“…This conclusion accords with our previous report on the intestinal absorption of calcium and magnesium in hepatobiliary disease in infancy (Kobayashi et al, 1974b). In the paper, it was shown that in biliary atresia parenteral vitamin D increased moderately the absorption of both elements, although oral vitamin D had little effect.…”
Section: Discussionsupporting
confidence: 92%
“…This conclusion accords with our previous report on the intestinal absorption of calcium and magnesium in hepatobiliary disease in infancy (Kobayashi et al, 1974b). In the paper, it was shown that in biliary atresia parenteral vitamin D increased moderately the absorption of both elements, although oral vitamin D had little effect.…”
Section: Discussionsupporting
confidence: 92%
“…Although absorption of calcium and fat were consistently lower in this subject than in the other five subjects, the absorption of other nutrients was not noticeably affected. Increased fecal excretion of fat (47)(48)(49) as well as impaired digestion of lactose (50, 5 1) have been shown to be associated with impaired absorption of calcium. However, if impaired absorption of fat or lactose had been the primary defect, one would have expected some recognizable clinical correlate and probably poor absorption of other nutrients.…”
Section: The Main Purpose O F This Study Was To Examine the Effect O mentioning
confidence: 99%
“…Bile is important for the intestinal absorption of calcium and magnesium because it is necessary for the absorption of vitamin D (Schachter, Finkelstein, and Kowarski, 1964), which enhances the absorption of both elements. Bone disease may be attributable to the malabsorption of these elements in hepatobiliary disease in which bile flow into the intestines is deficient or absent (Kobayashi et al, 1974). Furthermore, vitamin D that is absorbed from the gastrointestinal tract via the lymphatics and is transported from there to the liver in the chylomicron of the plasma may be hydroxylated in the liver to a more potent metabolite, 25-hydroxycholecalciferol (25-HCC) (Lund and DeLuca, 1966;Ponchon, Kennan, and DeLuca, 1969), which is thought to be converted to more active forms, 1, 25or 21,25or 21, in the kidneys (Fraser and Kodicek, 1970).…”
Section: Discussioñmentioning
confidence: 99%
“…Kobayashi et al (1974) showed that in biliary atresia oral vitamin D had little, if any, effect on the absorption of calcium and magnesium, though the vitamin moderately increased absorption when given intramuscularly. It is reasonable to conclude from these studies that vitamin D should be given intramuscularly to reduce the incidence and severity of rickets in this disorder.…”
Section: Discussioñmentioning
confidence: 99%